Where do ideas come from?: Seeking inspiration from inside – and outside – the firm. Issue 9 (10th September 2018) - Unknown
Abstract : Purpose: Reviews the latest management developments across the globe and pinpoints practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Where innovation starts from has given many authors the inspiration to write many books and articles attracting many readers. But how many of them really stick in the mind? It is always the exceptions that prove the rule that stick out, all the way from Archimedes in the bath through to Newton's apple and on to mobile phones based on Star Trek communicators. But while these make for a good story, they represent but a tiny fraction of all ideas that buzz around businesses throughout the world at any given time. For those of us that don't have a dramatic light bulb moment, where should we seek inspiration? Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.